Microplastics, potential threat to patients with lung diseases - Lu, Kuo; Zhan, Danting; Fang, Yingying; Li, Lei; Chen, Guobing; Chen, Shanze; Wang, Lingwei (Frontiers in Toxicology, 2022)
Air pollution is one of the major risk factors for lung disease. Microplastics are a ubiquitous environmental pollutant, both indoors and in outdoor air. Microplastics have been found in human lung tissue and sputum. However, there is a paucity of information on the effects and mechanisms of microplastics on lung disease. In this mini-review, we reviewed the possible mechanisms by which air microplastics exposure affects lung disease and, at the same time, pointed out the limitations of current studies.